(untitled) - Buckley, Peter J. (New York, N.Y., 2005)
What is international business? Is the international business research agenda running out of steam? These and other key questions are answered in this influential book which points to a definitive statement on International Business. Bringing together a variety of different perspectives, this book is a collection of the latest thinking from eminent scholars on the question of international business.
Keywords: International business enterprises; Management